(untitled) (CIPEEX, 2025)
Illegal mining in Brazilian lands has generated significant negative impacts since the colonial period, with the interiorization and search for precious stones and metals, which drastically increased from the 17th century due to expeditions known as bandeiras, led by sertanistas seeking mainly gold and silver, in a region that is vast in these resources. This study aims to analyze the socioeconomic qualities of regions with illegal mining activities. It is an integrative review of the literature regarding environmental and health issues in illegal mining among miners and the community. The descriptors "Health," "Environmental," "Mining," and "Illegal" were used in databases such as Google Scholar, SciELO, Brasil Escola, and WWF.Brasil, with full texts available in Portuguese (Brazil). Based on the analyses, the vulnerability of miners precedes risks and simultaneously determines what they are, both in the mining environment and in the relationships established from this work, that is, with the community. The presence of miners also increases the proliferation of diseases such as malaria, leishmaniasis, syphilis, and tuberculosis in these territories. Conflicts, aggression, and disputes in these regions contribute to the spread of STIs and other communicable diseases among this population. In summary, illegal mining is also strongly linked to increased deforestation, river sedimentation, land grabbing, and rising violence in its surroundings.